Development of the model to predict the growth of Salmonella amsterdam and Salmonella bangkok in stirred fried rice with crab meat - Songamnat Pongsomboon (2018)
Central Composite Design (CCD) was used to study the main factors (temperature, pH, salt concentration, initial innoculum and incubation time) affecting Salmonella enteritidis growth in stirred fried rice with crab meat (Khao Pad Pu). The result obtained from the CCD fitting by a second-order model, using a quadratic polynomial equation, was as follow: Y = 37.024-0.005 INOC + 7.7 x 10-7 INOC2 + 0.001 INOC. pH + 3.5x10-4 INOC.Time + 3.131 NaCl + 7.713 NaCl2 - 6.8x10-5 NaCl.INOC-2.20 NaCl.pH + 0.148 NaCl. Time-11.0 pH + 0.0927 pH2 + 0.037 pH.Time + 0.489 Temp-0.003 Temp2 -2.3x10-4 Temp. INOC- 0.056 Temp.NaCl- 0.019 Temp.pH+ 0.007 Time.Temp- 0.619 Time -6.00x10-4 Time2. R-square = 0.8659 This equation was used to predict the population of Salmonella amsterdam and Salmonella bangkok in Khao Pad Pu, growing under different conditions. The predicted values were compared with viable counts for validation. It was found that the R2 were 0.618 and 0.691 for S. amsterdam and S. bangkok, respectively.